1967
DOI: 10.1515/znb-1967-0504
|View full text |Cite
|
Sign up to set email alerts
|

Identifizierung der Radiolyseprodukte

Abstract: Single-phase Pr 2 CBr was prepared by heating a mixture of PrBr 3 , Pr and C (1 : 5:3) to 1140 • C for 18 d. The crystal structure was investigated by X-ray single crystal diffraction (space group P6 3 /mmc, a = 3.8071 (3), c = 14.7787(12)Å). In the structure the Pr atoms form C-centered octahedra condensed into Pr 2 C sheets via common edges; these sheets are separated by the Br atoms which are in a trigonal prismatic environment of Pr atoms. Pr 2 CBr is a black shiny compound with metallic conductivity. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

1969
1969
1980
1980

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
4
5
0
Order By: Relevance
“…Thus the t-butanol radical cannot be responsible for all the observed destruction of BU in N 2 -saturated solutions, and it can be concluded that eaq destroys BU irreversibly. This conclusion is supported by previously published data (Adams 1967, Reuschl 1966, Gilbert et al 1967.…”
Section: Comparison Of Reactions Of B U and T With Eaq-supporting
confidence: 90%
See 4 more Smart Citations
“…Thus the t-butanol radical cannot be responsible for all the observed destruction of BU in N 2 -saturated solutions, and it can be concluded that eaq destroys BU irreversibly. This conclusion is supported by previously published data (Adams 1967, Reuschl 1966, Gilbert et al 1967.…”
Section: Comparison Of Reactions Of B U and T With Eaq-supporting
confidence: 90%
“…Since the total G(OH' + H-) is -5-6, a fraction of the molecules attacked must be reconstituted to BU and T. Other studies on the radiolysis of aqueous T solutions have shown that OH-adds preferentially to the 5-6 carbon-carbon double bond and that the 5-6 glycol is a major radiolysis product (for example, see Ekert and Monier 1960). The corresponding glycol has been identified as a major product of OH-attack on BU in aqueous solution (Gilbert et al 1967). These data indicate that the reactions of OH-with BU and T are similar and support the hypothesis that OH-adds preferentially to the BU 5-6 carbon-carbon double bond.…”
Section: Reactions Of H-and Oh-with Bu and Tsupporting
confidence: 66%
See 3 more Smart Citations